Kontestasi Ideologi dalam Wacana #MBG di Instagram: Analisis Wacana Kritis Model Fairclough - Desma Yuliadi Saputra; Andriani, Rina (Universitas Insan Budi Utomo, 2026)
This study aims to examine the ideological contestation within the #MBG discourse on Instagram using Norman Fairclough’s Critical Discourse Analysis model. Social media, particularly Instagram, has become a digital public sphere where narratives of policy legitimation intersect with critical counter-narratives from the public. In this context, the #MBG discourse functions not merely as an informational medium but as a site of meaning struggle that reflects power relations and ideological interests. This research employs a qualitative approach within a critical paradigm. Data consist of Instagram posts containing the hashtag #MBG, selected purposively based on engagement level and issue relevance. The analysis applies Fairclough’s three-dimensional framework: textual analysis, discursive practice, and social practice. The findings reveal a polarization of representations between legitimizing narratives emphasizing policy success, efficiency, and public welfare orientation, and critical narratives highlighting issues of transparency, governance, and potential conflicts of interest. This contestation demonstrates that language in social media operates as an instrument for ideological reproduction and negotiation. The study underscores the importance of critical literacy in interpreting policy discourse within digital spaces to avoid partial and ideologically driven constructions of meaning.